A Journey into Other Faiths: The Experience of a Pentecostal Theologian - White, Peter (Interreligious studies and intercultural theology, 2023)
We live in a world of diversity, and so it is with people's religious beliefs and how they approach their religious practices in relation to a deity and their social and relational lives. Bible history has taught us that God has always allowed religious diversity. The biggest threat to the world is not poverty, health, and economic challenges but rather religious intolerance, the fear of compromising our faith, bias, and prejudice about other faiths. This article narrates the author's experience and journey as a Pentecostal scholar in dialogue with other faiths. It argues that it is possible to study other religions without losing one's own faith insofar as the various methods and principles for the study of religions can be applied. The article promotes the use of dialogue and spiritual discernment as tools to engage with people of other faiths. These approaches therefore become means of moving together toward life.